Can investors profit from mutual funds performance persistence? - Vital, Pedro Ribeiro Moreira Fezas (2016)
We use almost 21,000 equity mutual funds worldwide returns to provide evidence that investors can make significant profits if they invest in persistence strategies. Our regressions results are mixed and show some funds managers are better in picking stocks. We show that investors would have been delivered Annualized Sharpe Ratios up to 0.81. We also test our strategies under different economic environments and conclude that in expansion periods, our strategies outperform both S&P500 and MSCI. We also find our results still hold after deducting funds’ redemption fees, especially for holding periods longer than 3 months.